Diagnostic Roles of Neutrophil-to-Lymphocyte Ratio and Platelet-to-Lymphocyte Ratio for Vertebral Fracture due to Tuberculosis and Malignancy - Saragih, Iwan Vanca; Agus Priambodo (HM Publisher, 2025)
Background: Vertebral fracture is a serious complication that can occur due to various medical conditions, including bone tuberculosis and malignancy (eg, cancer metastasis to the vertebrae). This condition invariably causes an increase in the inflammatory process in the body, which can be identified through the Neutrophil-to-Lymphocyte Ratio (NLR) and Platelet-to-Lymphocyte Ratio (PLR). This study aims to investigate the differences in NLR and PLR values in patients with vertebral fractures due to TB or malignancy. Methods: A retrospective observational study was conducted on vertebral fracture patients who underwent surgery in the Orthopedic Surgery Department of Dr. Kariadi Hospital Semarang between January 1st, 2022, and December 31st, 2023. Data on demographics and laboratory test results were extracted from medical records. Statistical analysis was performed using univariate analysis and presented as percentage and frequency. T-test or Mann-Whitney test was used to determine the difference based on their normality distribution. The diagnostic value of NLR and PLR was also analyzed using the receiver operating characteristic (ROC) curve and Youden index. Results: The study included 54 vertebral fracture patients. The mean age of patients was 41.77 ± 16.00 years, and the majority were female patients (68.5%). The Neutrophil to Lymphocyte Ratio (NLR) value was significantly higher in vertebral fracture due to malignancy patients than TB (5.5 (IQR 3.92 – 13.39) vs 4.53 (IQR 2.91 – 6.96), p=0.020). In contrast, the Platelet to Lymphocyte Ratio (PLR) value was not significantly different (p>0.05). The area under the curve for the NLR (0.69, 95% confidence interval [CI], 0.54 – 0.839) was greater than that of PLR (0.408, 95% CI, 0.246 – 0.571). Conclusion: NLR showed significantly different results in determining the cause of vertebral fractures, either tuberculosis or malignancy. NLR can be used as an important diagnostic marker to help differentiate between vertebral fractures caused by malignancy and those caused by infection.